2016
DOI: 10.1016/j.surfcoat.2016.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on DLC coated micro moulds

Abstract: Microinjection moulding is a key enabling technology for replicating miniaturized components and parts with functional features at the micrometer and even submicrometer length scale. The micro moulding tools used in the process chain are critical for delivering high quality parts for the duration of the product life cycle, and recently tool coatings such as Diamond-like carbon (DLC) have been used to extend their use and enhance the performance. The micro injection moulding process has high injection speeds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Lastly, with the inherent volumetric change during the processing of polymers through µIM, interactions occur between processing variables such as injection pressure, shear stress, clamping force and friction between the resulting mould surface and polymer melt. As mentioned, this study follows on from the previous investigation analysing the difference in thermal expansion between the polymer melt and aC:H coated SS substrate [15]. Here, micro-indentations are purposely imposed upon the substrate to conclude the feasibility of DLC coatings within µIM.…”
Section: Superficial Thermal Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, with the inherent volumetric change during the processing of polymers through µIM, interactions occur between processing variables such as injection pressure, shear stress, clamping force and friction between the resulting mould surface and polymer melt. As mentioned, this study follows on from the previous investigation analysing the difference in thermal expansion between the polymer melt and aC:H coated SS substrate [15]. Here, micro-indentations are purposely imposed upon the substrate to conclude the feasibility of DLC coatings within µIM.…”
Section: Superficial Thermal Expansionmentioning
confidence: 99%
“…The research presented in this paper follows on from Griffiths et al [15]; where previous work where Finite Element Analysis (FEA) simulation was carried out on a micro-mould to identify areas of the tool surface that experiences sudden heat variation. The same substrate was used with the deposition of a aC:H coating on a Stainless Steel (SS) micromould in order to investigate how the coating withstood thermal cycling.…”
Section: Introduction*mentioning
confidence: 99%
“…Schoenherr et al 26 designed a novel mold for measuring adhesion forces, enabling a more accurate measurement of demolding forces. Griffiths et al 27 investigated the effects of melt temperature, mold temperature, and packing pressure on the demolding force of COC by using a condition monitoring mold and found that temperature had the greatest effect on the demolding work. Sorgato et al 28 concluded that the peak demolding force was positively correlated with the static friction by evaluating the performance of different coatings in offline friction tests.…”
Section: Introductionmentioning
confidence: 99%
“…This could increase the tool life by preventing delamination, cracking and coating failures. However, a good adhesion between the DLC coating and the mould is necessary and a proper selection of the tooling material, thermoplastics and moulding process parameters is required [8]. Additionally, due to DLC's lubricating properties and low surface roughness, the ejection forces in microinjection moulding of components with large area to volume ratios surfaces can be decreased significantly [9].…”
Section: Introductionmentioning
confidence: 99%